Biogeochemical cycling of manganese and iron in a macrotidal and hyperturbid estuary subject to flow-driven sedimentation - Mohammed Barhdadi; Aurélia Mouret; Christine Barras; Sabine Schmidt; Grégoire M. Maillet; Nour El Imene Boukortt; Meryem Mojtahid; Matthieu Durand; Bruno Deflandre; Corentin Guilhermic; Aubin Thibault de Chanvalon; Sylvain Rigaud; et al. (Chemical Geology, 2024)

Ecotoxicity of single and mixture of perfluoroalkyl substances (PFOS and PFOA) in soils to the earthworm Aporrectodea caliginosa - L. Delor; M. Louzon; C. Pelosi; E. Michel; G. Maillet; H. Carronnier (Environmental Pollution, 2023)

Impact of an exceptional winter flood on benthic oxygen and nutrient fluxes in a temperate macrotidal estuary: Potential consequences on summer deoxygenation - Vivien Hulot; Edouard Metzger; Aubin Thibault de Chanvalon; Aurelia Mouret; Sabine Schmidt; Bruno Deflandre; Sylvain Rigaud; Eric Beneteau; Nicolas Savoye; Philippe Souchu; Yoann Le Merrer; Grégoire M. Maillet (Frontiers in Marine Science, 2023)
Despite 20 years of control on eutrophication, episodes of summer hypoxia still occur in the Loire estuary, impacting water quality and posing a key scientific and management challenge. This work aimed to quantify the contribution of the benthic compartment to hypoxia in the Loire estuary by direct measurement of water–sediment fluxes and an in-depth understanding of the seasonal variations of oxides and phosphorus stocks. During the summer’s low-discharge period, results show that the iron oxide-rich deposit is stable under hypoxic conditions, limiting the release of dissolved phosphorus into the overlying water column. The high nitrate content of the water column appears to be an important oxidizer of iron during hypoxic periods, limiting dissolved phosphorus leakage and aggravation of hypoxia. During the exceptional winter flood, significant sediment erosion associated with bubbling phenomena (attributed to methane efflux) created severe fractures in the sediment and stimulated water–sediment exchange. During the following months, these fractures were progressively filled, which decreased the intensity of benthic fluxes. However, due to the high residence time in the water during the summer period, a simple model demonstrated that benthic contributions were sufficient to directly (by direct oxygen consumption) or indirectly (by promoting ammonia oxidation) affect the oxygen stock in the water column during the low-discharge period. Our study demonstrates the importance of the benthic compartment in the occurrence of hypoxia and the obvious lack of knowledge to illustrate and model the biogeochemical functioning of the estuary.

Impact of therapeutic drug monitoring of antibiotics in the management of infective endocarditis - G. Macheda; N. El Helali; G. Péan de Ponfilly; M. Kloeckner; P. Garçon; M. Maillet; V. Tolsma; C. Mory; A. Le Monnier; B. Pilmis (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

The killer within: Endogenous bacteria accelerate oyster mortality during sustained anoxia - Michael R. S. Coffin; Jeff C. Clements; Luc A. Comeau; Thomas Guyondet; Michelle Maillet; Laura Steeves; Keryn Winterburn; José M. F. Babarro; Martin A. Mallet; Rémy Haché; Luke A. Poirier; Saswati Deb; et al. (Limnology and Oceanography, 2021)
Sustained periods of anoxia, driven by eutrophication, threaten coastal marine systems and can lead to mass mortalities of even resilient animals such as bivalves. While mortality rates under anoxia are well‐studied, the specific mechanism(s) of mortality are less clear. We used a suite of complementary techniques (LT50, histology, 16S rRNA amplicon sequencing, and valvometry) to show that the proliferation of anaerobic bacteria within eastern oysters ( Crassostrea virginica ) accelerates mortality rate under anoxic conditions. Manipulative laboratory experiments revealed that oyster survival under anoxic conditions was halved when bacteria were present compared to when they were excluded by the broad‐spectrum antibiotic chloramphenicol. Histological assessments supported this mechanism and showed infiltration of bacteria in oysters that were not treated with antibiotics compared to a general lack of bacteria when oysters were treated with antibiotics. 16S rRNA amplicon sequencing failed to identify any particular genera of bacteria responsible for mortality, rather a diversity of endogenous anaerobic and/or sulfate‐reducing bacteria were common among oysters. In addition, monitoring of oyster valve gaping behavior in the field revealed that oysters showed remarkable valve closure synchrony when first exposed to anoxia. However, oysters periodically opened throughout anoxia/hypoxia in both the lab and field, suggesting that the infiltration of exogenous bacteria from the environment may also influence mortality rates under natural settings. Coupled with previous studies, we posit that mass mortality events in a wide range of coastal bivalves are likely the result of co‐morbidity from asphyxiation and bacterial processes.

Human locomotion with reinforcement learning using bioinspired reward reshaping strategies - Katharine Nowakowski; Philippe Carvalho; Jean-Baptiste Six; Yann Maillet; Anh Tu Nguyen; Ismail Seghiri; Loick M’Pemba; Theo Marcille; Sy Toan Ngo; Tien-Tuan Dao (Medical & Biological Engineering & Computing, 2021)

Safety, tolerability, pharmacokinetics, and pharmacodynamics of low dose lysergic acid diethylamide (LSD) in healthy older volunteers - Neiloufar Family; Emeline L. Maillet; Luke T. J. Williams; Erwin Krediet; Robin L. Carhart-Harris; Tim M. Williams; Charles D. Nichols; Daniel J. Goble; Shlomi Raz (Psychopharmacology, 2020)
Abstract Research has shown that psychedelics, such as lysergic acid diethylamide (LSD), have profound anti-inflammatory properties mediated by 5-HT 2A receptor signaling, supporting their evaluation as a therapeutic for neuroinflammation associated with neurodegenerative disease. Objective This study evaluated the safety, tolerability, pharmacokinetics, and pharmacodynamics of orally repeated administration of 5 μg, 10 μg, and 20 μg LSD in older healthy individuals. In the current paper, we present safety, tolerability, pharmacokinetics, and pharmacodynamic measures that relate to safety, tolerability, and dose response. Methods This was a phase 1 double-blind, placebo-controlled, randomized study. Volunteers were randomly assigned to 1 of 4 dose groups (5 μg, 10 μg, 20 μg LSD, and placebo), and received their assigned dose on six occasions (i.e., every 4 days). Results Forty-eight older healthy volunteers (mean age = 62.9 years) received placebo ( n = 12), 5 μg ( n = 12), 10 μg ( n = 12), or 20 μg ( n = 12) LSD. LSD plasma levels were undetectable for the 5 μg group and peak blood plasma levels for the 10 μg and 20 μg groups occurred at 30 min. LSD was well tolerated, and the frequency of adverse events was no higher than for placebo. Assessments of cognition, balance, and proprioception revealed no impairment. Conclusions Our results suggest safety and tolerability of orally administered 5 μg, 10 μg, and 20 μg LSD every fourth day over a 21-day period and support further clinical development of LSD for the treatment and prevention of Alzheimer’s disease (AD).

Prolonged suppressive antibiotic therapy for prosthetic joint infection in the elderly: a national multicentre cohort study - V. Prendki; T. Ferry; P. Sergent; E. Oziol; E. Forestier; T. Fraisse; S. Tounes; S. Ansart; J. Gaillat; S. Bayle; O. Ruyer; F. Borlot; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Is brain angio-MRI useful in infective endocarditis management? - J. Champey; P. Pavese; H. Bouvaist; M. Maillet; A. Kastler; B. Boussat; P. Francois (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Is prosthesis retention effective for chronic infections in hip arthroplasties? A systematic literature review - M. Maillet; P. Pavese; D. Bruley; A. Seigneurin; P. François (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Evaluation of an intervention to improve blood culture practices: a cluster randomised trial - P. Pavese; M. Maillet; V. Vitrat-Hincky; C. Recule; J.-P. Vittoz; A. Guyomard; A. Seigneurin; P. François (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Pneumocystis jirovecii (Pj) quantitative PCR to differentiate Pj pneumonia from Pj colonization in immunocompromised patients - M. Maillet; D. Maubon; J. P. Brion; P. François; L. Molina; J. P. Stahl; O. Epaulard; A. Bosseray; P. Pavese (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Telomere-length regulation in inter-ecotype crosses of Arabidopsis - G. Maillet; C. I. White; M. E. Gallego (Plant Molecular Biology, 2006)

High Resolution Electrical Resistivity Tomography (ERT) in a Transition Zone Environment: Application for Detailed Internal Architecture and Infilling Processes Study of a Rhône River Paleo-channel - Grégoire M. Maillet; Enzo Rizzo; André Revil; Claude Vella (Marine Geophysical Research, 2005)